Formulation And Evaluation Of Rizatriptan Benzoate Mouth Dissolving Tablets Using Natural Superdisintegrants - Abid, Md Ather Ahmed; Chukka, Saritha (Journal of Neonatal Surgery, 2025)
Introduction: Rizatriptan benzoate is a new generation anti-migraine drug, potent and selective 5-hydroxy tryptamine 1B/1D receptor agonist used for the treatment of acute migraine attack. The bioavailability of Rizatriptan benzoate is about 45%. The half-life is 2 to 3 hours. The aim of the study was to formulate Rizatriptan benzoate mouth dissolving tablets (MDT) to enhance the dissolution rate to facilitate quick onset of action. Methods: Total nine formulations were developed by direct compression method using three natural super-disintegrants. DSC was conducted to study the drug-excipient interaction. All the formulations were subjected for in vitro evaluation tests. Stability study was performed on optimized formulation for 6 months period of time. Results: All the developed formulations were lies within the pharmacopeia limits. Based on the disintegration time and drug release studies, F3 formulation was selected as optimized formulation. Further, it was subjected for stability studies and was stable for a period of 6 months. Conclusion: Rizatriptan benzoate mouth dissolving tablets were successfully prepared by the direct compression method using karaya gum, xanthan gum and plantago ovata as superdisintegrants. The optimized formulation (i.e., F3) showed fast disintegration, highest dissolution and was stable for 6 months.